Waanwezig-heden. - Késenne, Joannes; Sint-Truiden (Genk : Centrum Bruno Renson vzw, 2004)
Aerts, José ; Carlier, Jan ; Daems, Walter ; De Konick, Peter ; d'O, Honoré ; Duchateau, Hugo ; Green, Scott ; Hoeben, Marcel ; Holtappels, Jos ; Lipkens, René ; Renard, Thierry ; et al.
Sint-Truiden, verschilende locaties, 15 oktober - 14 november 2004
kunstcatalogus